Applied History and Contemporary Policymaking : School of Statecraft - Crowcroft, Robert (London [England] : Bloomsbury Academic, 2022)
"Robert Crowcroft has assembled a world-class, international cast of outstanding scholars and international figures to produce a stimulating collection of essays on applied history and policy making. With contributors such as David Petraeus, former Director of the Central Intelligence Agency, and endorsed by Henry Kissinger, former US Secretary of State, this collection of essays addresses some of the most important geopolitical challenges confronting the world today. From reconstructing collapsed political regimes to security competition in the China Seas and the evolution of Salafi-Jihadi ideology, it explores a range of statecraft, policy and strategy. The essays span a number of policy areas and historical problems, tackling important questions about what historians do (and should do), and considering the nature and limits of historical judgement. With some examining how applied history can be used to rethink contemporary challenges, others explore how it has been used and abused in the past. Making a splash in intellectual debate by making a definitive case for Applied History, this book demonstrates that a knowledge of the past, and the insight it provides, is imperative to effective statecraft."--
Introduction: The Tiger in the Grass / (Robert Crowcroft) -- Part I: The American World Order in Crisis. 1. The Changing Nature of the State / (Philip Bobbitt) ; 2. In Need of An Enemy? The Liberal World Order and its Survival / (Robert Crowcroft) ; 3. Applied History and Contemporary American Foreign Policy / (David Petraeus and Kori Schake) ; 4. The British Roots of American Strategic Culture / (Giselle Donnelly) ; 5. Theodore Roosevelt, History, and the Practice of US Statecraft / (Charlie Laderman) -- Part II: The British State and the Practice of Applied History. 6. Institutional Memory and the Lessons of History: Sir Maurice Hankey and the British 'War Book' / (Francesca Morphakis). ; 7. Charles Webster and the Development of the United Nations / (Andrew Ehrhardt). ; 8. Britain and the Construction of 'Europe' / (Rogelia Pastor-Castro) ; 9. Problems Left Over from History / (Lord Peter Ricketts) -- Part III: Looking Forward and Back. 10. History as Guardian of Constitutions / (Harshan Kumarasingham) ; 11. Navigating a Minefield: Law and the Past / (Richard A. Epstein) ; 12. Nation-Building as Applied History / (Jeremi Suri) ; 13. Security Competition in the China Seas / (Kun-Chin Lin) ; 14. The Evolution of Salafi-Jihadi Ideology / (Shiraz Maher) ; 15. Learning from Military History? / (Jeremy Black) ; 16. Comparative History and Strategy: Why a Carthage is now Likely to Defeat a Rome / (Paul Rahe) ; 17. When Reason Replaces Wisdom: The Neglect of History and Statesmanship, and the Decline of Political Science / (Steven F. Hayward)
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Geopolitics -- History; World history; Electronic books